Review of Game Theory Applications in International Trade - Khurana, Chaitanya (International Journal of English Literature and Social Sciences (IJELS), 2022)
Game theoretical models have been applied to various fields of economics over the years and has helped in formulating simple models for complex economic scenarios. On such field where these models have been found out to be very useful is the domain of International trade. This paper is a review paper on game theoretical models being applied in international trade for analysing trade wars, trade policy and complex tradenegotiations. The paper also has reviewed game theory models being applied to US China trade war. The paper has tried to review almost every important game theory model which has been useful in finding out optimum results and helping countries make the best policy decisions related to international trade.